2014
DOI: 10.4018/ijaci.2014070101
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Utilization of Automata in Representing Players' Behaviors in Game Theory

Abstract: Representing players' strategies in game theory has a direct impact on the players' performance. The state of art shows that automata are one of the primary techniques used for representing players' strategies and behaviors. In this paper, the author will identify different types of automata and assess their utilization in the field of game theory. Is has been found that finite automata, adaptive automata, and cellular automata are widely adopted in game theory. The utilization of finite automata is found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Subsequently, Meyer used quantum lattice gas automata to study Parrondo games in [21]. The application of probabilistic automata in the prisoners' dilemma game was undertaken in [22], while [23] considered the use of different automata variants in game theory. In [24] it was pointed out that quantum automata operating on infinite words can encode winning strategies for abstract quantum games.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently, Meyer used quantum lattice gas automata to study Parrondo games in [21]. The application of probabilistic automata in the prisoners' dilemma game was undertaken in [22], while [23] considered the use of different automata variants in game theory. In [24] it was pointed out that quantum automata operating on infinite words can encode winning strategies for abstract quantum games.…”
Section: Related Workmentioning
confidence: 99%
“…They also gave their assessment about possible future developments in this field and their impact on information processing. Recently, Suwais [27] examined different types of automata variants and reviewed the use for each one of them in game theory. In a similar vein, Almanasra et al [28] reported that finite automata are suitable for simple strategies whereas adaptive and cellular automata can be applied in complex environments.…”
Section: Related Workmentioning
confidence: 99%
“…Evolutionary game theory is a theory that combines game theory analysis and between members of the multi-agent system [32]. Khaled applied automata to game theory [33]. Abram studied the Nash equilibrium of the game, and made static and dynamic evolution analysis [34].…”
mentioning
confidence: 99%